PENGARUH LAMA RETENSI AIR TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis Niloticus) PADA BUDIDAYA SISTEM AKUAPONIK DENGAN TANAMAN KANGKUNG [Effect of Water Retention On The Growth Rate of Nile Tilapia (Oreochromis niloticus) In The Aquaponic System Planted Water Spinach (Ipomoea reptans)] - Setijaningsih, Lies; Umar, Chairulwan (BERITA BIOLOGI, 2015)
In principle, fish culture with aquaponics system save land utilization and can improve the efficiency of nutrient utilization of unconsumed feed and fish metabolism waste. Therefore, this system is recognized as environmentally friendly fish farming. The research aimed to find the optimum water retention for the maximum growth of tilapia raised in the aquaponics system. This experiment consisted of three treatments of different water retention, i.e. 30, 60, and 120 minutes and one flow- through recirculation system. Results showed that the highest individual weight gain of 39.92 g and individual daily growth rate of 0.54 g /day were reached in the treatment of 120 minutes water retention for 40 days growing period. Meanwhile, the lowest individual weight were observed in the treatment of 30 minutes water retention and control treatment, i.e. 25.25 ± 1.22 g and 18.52 ± 1.07 g, respectively. Aquaponic fish farming system with water retention of 120 minutes could reduced 10.69% of N- Total and 38.10% of P- Total, while survival rate was not influenced by water retention treatment